Functional respiratory imaging (FRI) for optimizing therapy development and patient care. (1st February 2016) - Hajian, Bita; De Backer, Jan; Vos, Wim; Van Holsbeke, Cedric; Clukers, Johan; De Backer, Wilfried
Abstract: Functional imaging techniques offer the possibility of improved visualization of anatomical structures such as; airways, lobe volumes and blood vessels. Computer-based flow simulations with a three-dimensional element add functionality to the images. By providing valuable detailed information about airway geometry, internal airflow distribution and inhalation profile, functional respiratory imaging can be of use routinely in the clinic. Three dimensional visualization allows for highly detailed follow-up in terms of disease progression or in assessing effects of interventions. Here, we explore the usefulness of functional respiratory imaging in different respiratory diseases. In patients with asthma and COPD, functional respiratory imaging has been used for phenotyping these patients, to predict the responder and non-responder phenotype and to evaluate different innovative therapeutic interventions.